2000
DOI: 10.1136/thorax.55.4.302
|View full text |Cite
|
Sign up to set email alerts
|

Automated analysis of digital oximetry in the diagnosis of obstructive sleep apnoea

Abstract: Background-The gold standard diagnostic test for obstructive sleep apnoea (OSA) is overnight polysomnography (PSG) which is costly in terms of time and money. Consequently, a number of alternatives to PSG have been proposed. Oximetry is appealing because of its widespread availability and ease of application. The diagnostic performance of an automated analysis algorithm based on falls and recovery of digitally recorded oxygen saturation was compared with PSG. Methods-Two hundred and forty six patients with sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
178
1
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(195 citation statements)
references
References 18 publications
6
178
1
4
Order By: Relevance
“…However, there is good evidence that equivalence exists between the two measures of OSAS severity [49], and indeed ODI is at least as reproducible as the AHI between repeated nights [50]. Furthermore, oscillations in oxygen levels may be more pertinent to the vascular effects of OSA than apnoeic events [51] and therefore the current authors believe that the use of an ODI rather than an AHI does not limit the interpretation of their data.…”
Section: Study Limitationsmentioning
confidence: 86%
“…However, there is good evidence that equivalence exists between the two measures of OSAS severity [49], and indeed ODI is at least as reproducible as the AHI between repeated nights [50]. Furthermore, oscillations in oxygen levels may be more pertinent to the vascular effects of OSA than apnoeic events [51] and therefore the current authors believe that the use of an ODI rather than an AHI does not limit the interpretation of their data.…”
Section: Study Limitationsmentioning
confidence: 86%
“…This large number of tests dictated that we use automatic scoring in the interest of efficiency and reliability. The Snore Sat Recorder used in this study has been shown to correlate well with a polysomnogram-determined respiratory disturbance index (r 2 = 0.97) 47 suggesting that the recorder provides a reliable index of the full-night frequency of respiratory disturbances. Furthermore, the oxygen component used in the scoring of ODI is less prone to uncontrolled variability and noise than the ventilatory component used in the scoring of AHI.…”
Section: Ppv 97% Npv 72%mentioning
confidence: 93%
“…Specifically, all participants underwent a 2-night feedback-controlled mandibular positioning (FCMP) study, and all received a custom treatment appliance. All participants underwent outcome testing with the treatment appliance in the mouth for 2 nights in the home using a validated monitor 47 that automatically calculates a 4% ODI. Therapeutic success or failure was defined as a mean ODI value from the 2 outcome studies of less or greater than 10 events/h, respectively.…”
Section: Generalmentioning
confidence: 99%
“…We proposed using the alternative of "selective" polysomnography in the highest-risk group of commercial drivers(1) by first identifying drivers most likely to have apnea with questionnaire and oximetry (15). The questionnaire we used, the multivariable apnea prediction (16,17), predicts likelihood of apnea by combining three symptom-frequency questions with body mass index (BMI), age and gender.…”
Section: Diagnosing Apneamentioning
confidence: 99%